Assessing the Burden of Neglected Tropical Diseases in Low-Income Communities: Challenges and Solutions - Francesco Branda; Abdisalam Yusuf Ali; Giancarlo Ceccarelli; Mattia Albanese; Erica Binetti; Marta Giovanetti; Massimo Ciccozzi; Fabio Scarpa (Viruses)
Neglected tropical diseases (NTDs) represent a group of chronic and debilitating infections that affect more than one billion people, predominantly in low-income communities with limited health infrastructure. This paper analyzes the factors that perpetuate the burden of NTDs, highlighting how poor health infrastructure, unfavorable socioeconomic conditions and lack of therapeutic resources exacerbate their impact. The effectiveness of current interventions, such as mass drug administration (MDA) programs and improved sanitation, in reducing disease prevalence is examined. In addition, the role of climate change, which alters transmission dynamics and expands affected territories, is discussed as an emerging challenge. The analysis suggests that integrated, multisectoral approaches, including health education and infrastructure interventions, are essential to breaking the cycle of poverty and disease. Although international programs have marked significant progress, achieving elimination targets by 2030 requires sustained commitment, innovation, and increased research capacity in endemic countries.